Graphene nanoplatelets reinforced AgCuTi composite filler for brazing SiC ceramic. Issue 4 (April 2019) - Song, Yanyu; Liu, Duo; Hu, Shengpeng; Song, Xiaoguo; Cao, Jian
Abstract: Graphene nanoplatelets (GNPs) were used as reinforcement in AgCuTi filler for brazing SiC ceramic. Ti from the filler reacted with SiC ceramic to form TiC and Ti5 Si3 adjacent to the SiC ceramic. According to the TEM and HRTEM results, TiC layer exhibited good lattice matching with SiC substrate. TiC particles synthesized by the reaction between Ti and GNPs in situ promoted the heterogeneous nucleation of TiCu and Cu(s, s), and contributed to the refinement of microstructure. Shear tests results indicated that the adoption of GNPs affected the joint property significantly. The TiC particles and an appropriate TiC + Ti5 Si3 layer thickness both relieved the residual stress of the brazed joint and thereby increased the joint strength. The shear strength of the joint reached the maximum value of 38 MPa when using AgCuTi/GNPs (GNPs reinforced AgCuTi) composite filler containing 1% GNPs, which was ∼139% higher than that of the joint brazed with AgCuTi filler.